Peran Madrasah Diniyyah dan Pesantren Sebagai Subjek Hukum dalam Pembangunan Nasional Berbasis Pancasila - Nabila Nurfianda; Ahmad Muhammad Mustain Nasoha; Azizah Nur Fadilah; Nabila Salsabila; Radela Neva Kusuma (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Madrasah diniyyah and pesantren in the Indonesian context have often been viewed as non-formal or religious educational institutions, rather than as active legal subjects in national development. However, regulatory transformations and contextual challenges have prompted the need for legal recognition of these institutions in order to align them with the ideals of Pancasila. This study aims to analyze the role of madrasah diniyyah and pesantren. The methods used are normative and comparative qualitative research with a review of legislation and case studies of madrasah diniyyah/pesantren. The findings show that although regulations (e.g., the Pesantren Law) have provided legal recognition, there are still structural obstacles in the form of differences in institutional status, administrative capacity, and interpretative conflicts of values. On the other hand, several pesantren have successfully reconstructed themselves as actors of local development through community empowerment programs. In conclusion, legal recognition needs to be strengthened through the formulation of complementary regulations, institutional capacity building, and synergy between the government and pesantren communities so that these institutions can become pillars of national development based on Pancasila.